2020
DOI: 10.1038/s41598-020-60056-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of defensive secretion of a milkweed bug Lygaeus equestris by 1D GC-MS and GC×GC-MS: sex differences and host-plant effect

Abstract: The composition of defensive secretion produced by metathoracic scent glands was analysed in males and females of the milkweed bug Lygaeus equestris (Heteroptera) using gas chromatography with mass spectrometric detection (GC-MS). The bugs were raised either on cardenolide-containing Adonis vernalis or on control sunflower seeds in order to determine whether the possibility to sequester cardenolides from their host plants would affect the composition of defensive scent-gland secretion. Profiles of the composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Since endogenous and sequestered defenses may trade‐off (Engler‐Chaouat & Gilbert, 2007 ), the lack of cardenolides for sequestration could lead to a higher investment towards endogenous defenses (i.e., defensive secretions) and therefore impair growth on the cardenolide‐free control diet. Although such a trade‐off has been suggested to occur in the milkweed bug Lygaeus equestris (Havlikova et al, 2020 ), metathoracic scent glands were shown to be reduced in O . fasciatus and other milkweed bugs (Aldrich, 1988 ; Schaefer, 1972 ) making this explanation rather unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Since endogenous and sequestered defenses may trade‐off (Engler‐Chaouat & Gilbert, 2007 ), the lack of cardenolides for sequestration could lead to a higher investment towards endogenous defenses (i.e., defensive secretions) and therefore impair growth on the cardenolide‐free control diet. Although such a trade‐off has been suggested to occur in the milkweed bug Lygaeus equestris (Havlikova et al, 2020 ), metathoracic scent glands were shown to be reduced in O . fasciatus and other milkweed bugs (Aldrich, 1988 ; Schaefer, 1972 ) making this explanation rather unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…In the Parkinson’s disease rat model experiment, it was also found that the content of 1-octen-3-ol in the blood increased significantly, at the same time, decreasing in striatum homogenate . ( Z )-2-Octen-1-ol is a pheromone associated with the adult male locust, Schistocerca americana, and isomer ( E )-2-octen-1-ol, in addition to being a sexually attractive pheromone substance, is also a major component of insect defensive secretions …”
Section: Resultsmentioning
confidence: 96%
“…22 (Z)-2-Octen-1-ol is a pheromone associated with the adult male locust, Schistocerca americana, 23 and isomer (E)-2-octen-1-ol, in addition to being a sexually attractive pheromone substance, is also a major component of insect defensive secretions. 24 1-Octen-3-ol and (Z)-2-octen-1-ol were detected in linoleic acid side chain and arachidonic acid side chain-oxidized phosphatidylcholine standards, 15 respectively, and 1-octen-3one was present in both standards. It indicated that these three VOCs belong to C8 chain substances produced by the oxidation of C18−C20 unsaturated fatty acids, but these three VOCs have not been reported in human studies so far.…”
Section: ■ Materials and Methodsmentioning
confidence: 92%
“…This has contributed to the hypothesis that diet specialization would often lead to an evolutionary and ecological ‘dead end’. With the advances of analytical chemistry and metabolomic approaches, we are now seeing that many insects can biosynthesize specialized metabolites [28,29], modify plant-acquired compounds [35] and even recycle them [27]. Our findings highlight that biochemical plasticity is not only possible, it may be more prevalent than currently assumed, and it may have far-reaching consequences for diet breadth, ecological niche partitioning and speciation.…”
Section: Discussionmentioning
confidence: 92%
“…For example: Chrysomela lapponica larvae (Coleoptera) increase 40 fold synthesis of defensive esters when effective sequestration of salicylic glycoside is not possible [30]. When raised on milkweed, Lygaeus equestris (Heteroptera) sequester cardenolides and reduce biosynthesis of volatile defences in their scent-gland in comparison to bugs fed sunflower seeds (no cardenolides) [31]. Even though in these examples autogenous and sequestered defence compounds belong to completely divergent chemical classes and are likely under different selection forces, there is still a trade-off between biosynthesis and sequestration.…”
Section: Discussionmentioning
confidence: 99%